Habitat selection by European badgers in Mediterranean semi-arid ecosystems (Journal of Arid Environments, 2012)
We studied the habitat selection patterns of badgers Meles meles (Linnaeus, 1758) in Mediterranean semiarid ecosystems. Fifty-seven plots were sampled in two semi-arid regions of Spain. In each plot, badger latrines were located along 2.6 km transects. The number of badger latrines per km was used as a surrogate of badger abundance and as an index of habitat selection by badgers. For each plot, a series of environmental variables were measured at two spatial scales. These variables were related to land use and vegetation formation parameters that are considered potentially important for habitat requirements (i.e., food and shelter). The habitat selection model was carried out using generalised linear models (GLM) and an information-theoretic approach. Results indicated that badgers prefer fruit orchards, and shrub and rock-covered areas, which provide additional trophic and shelter resources, and avoid intensively cultivated ﬁelds and human settlements. We conclude that badger conservation in semi-arid environments of the Iberian Peninsula requires the existence of fruit orchards and the limitation of human development. Policies restraining agriculture intensiﬁcation would encourage traditional or new non-intensive agricultural practices and increase shrub-patch availability, which would beneﬁt this species.